Transoesophageal ultrasound and computer tomographic assessment of the equine cricoarytenoid dorsalis muscle: Relationship between muscle geometry and exercising laryngeal function. (26th February 2016) - Kenny, M.; Cercone, M.; Rawlinson, J. J.; Ducharme, N. G.; Bookbinder, L.; Thompson, M.; Cheetham, J.
Summary: Reasons for performing study: Early detection of recurrent laryngeal neuropathy (RLN) is of considerable interest to the equine industry. Objectives: To describe two imaging modalities, transoesophageal ultrasound (TEU) and computed tomography (CT) with multiplanar reconstruction to assess laryngeal muscle geometry, and determine the relationship between cricoarytenoid dorsalis (CAD) geometry and function. Study design: Two‐phase study evaluating CAD geometry in experimental horses and horses with naturally occurring RLN. Methods: Equine CAD muscle volume was determined from CT scan sets using volumetric reconstruction with LiveWire. The midbody and caudal dorsal‐ventral thickness of the CAD muscle was determined using a TEU in the same horses; and in horses with a range of severity of RLN (n = 112). Results: Transoesophageal ultrasound was able to readily image the CAD muscles and lower left:right CAD thickness ratios were observed with increasing disease severity. Computed tomography based muscle volume correlated very closely with ex vivo muscle volume (R 2 = 0.77). Conclusions: Computed tomography reconstruction can accurately determine intrinsic laryngeal muscle geometry. A relationship between TEU measurements of CAD geometry and laryngeal function was established. These imaging techniques could be used to track the response of the CAD muscle to restorative surgical treatments such as nerve muscle pedicle graft, nerve anastomosis and functional electrical stimulation.